A content analysis of Chinese news coverage on COVID-19 and tourism. Issue 2 (17th January 2022) - Chen, Honglin; Huang, Xia; Li, Zhiyong
ABSTRACT: News coverage plays a significant role in the tourism industry. 2019 Coronavirus Disease (COVID-19) has severely affected the tourism-related businesses and has been featured in Chinese news coverage. This research studied 499 newspaper articles through automated content analysis. Nine key themes were identified, including COVID-19's impact on tourism, people's sentiment, control of tourism activities and cultural venues, the role of the hospitality industry, national command and local response, tourism disputes and solutions, corporate self-improvement strategies, government assistance, and post-crisis tourism product. This research provides insights into future investigations of the tourism crisis related to an epidemic.